Pleuropulmonary aspergillosis presenting as hydropneumothorax in second trimester pregnancy - Selvi Chinnasamy; L Sundararajan; Charumathi Radhakrishnan; P Senthur Nambi (Indian Journal of Respiratory Care, 2019)
Pleuropulmonary aspergillosis is a rare entity and usually occurs in a patient with preexisting lung disease or surgery. A 29-year-old pregnant woman with 16 weeks of gestation presented with shortness of breath, right-sided chest pain, and productive cough of 2 weeks' duration. A chest radiograph done with abdominal shield revealed right hydropneumothorax. Intercostal drainage insertion was done under ultrasound guidance. Pleural fluid was exudative with high adenosine deaminase levels, and GeneXpert test was negative for Mycobacterium tuberculosis. Pleural fluid and sputum culture revealed significant growth of Aspergillus fumigatus. She was treated with voriconazole intravenously followed by oral route. The patient improved clinically with good lung expansion, and she delivered a normal live baby by elective cesarean section. We report this case in view of the rarity of pleuropulmonary aspergillosis occurring in a young pregnant female with no evidence of prior lung pathology.